Understanding and Level of Payment Gateway Usage on the Financial Performance of MSMEs in Palu City - Salomita, Irenes; Totanan, Chalarce; Yamin, Nina Yusnita (Universitas KH. Abdul Chalim Mojokerto, 2026)
Digital transformation encourages Micro, Small, and Medium Enterprises (MSMEs) to adopt electronic payment systems, including payment gateways, to improve transaction efficiency and financial performance. However, the use of this technology is not optimal in Palu City due to the low understanding and level of use. This study aims to analyze the influence of understanding and the level of payment gateway use on the financial performance of MSMEs. The research method uses a quantitative approach with a survey design. A sample of 344 MSMEs was selected using a simple random sampling technique with a margin of error of 5%. Data were analyzed using multiple linear regression through SPSS accompanied by validity, reliability, and classical assumption tests. The results of the study show that the understanding of MSME actors does not have a significant effect on financial performance. On the other hand, the level of payment gateway usage has a positive and significant effect on the financial performance of MSMEs. These findings prove that the improvement of financial performance is not only determined by knowledge of technology, but more determined by the intensity of the use of payment gateways in business transactions. Therefore, increasing digital literacy needs to be accompanied by practical use assistance so that MSMEs can get optimal benefits from transaction digitization.